‘There’s no music on a dead planet’: The role of Green Music Australia in climate change activism - Rickwood, Julie (Perfect Beat, 2021)
The article focuses on how popular music, environmental activism and climate change blend in the work of Green Music Australia through its projects and the networks it establishes within the music industry. The article describes a contextual background; broadly explores the links between popular music, environmental activism and climate change; and considers the notion of collective action. It concentrates on Green Music Australia by investigating the framing of its political and cultural imperative for climate activism. The article concludes with a reflection that includes the Global Climate Strike.